2022
DOI: 10.3390/nu14020264
|View full text |Cite
|
Sign up to set email alerts
|

Weight Change during the Early Phase of Convalescent Rehabilitation after Stroke as a Predictor of Functional Recovery: A Retrospective Cohort Study

Abstract: It has been reported that weight gain at discharge compared with admission is associated with improved activities of daily living in convalescent rehabilitation (CR) patients with low body mass index. Here, we investigated whether weight maintenance or gain during the early phase of CR after stroke correlates with a better functional recovery in patients with a wide range of BMI values. We conducted this retrospective cohort study in a CR ward of our hospital and included adult stroke patients admitted to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Additionally, the proportion of patients experiencing weight gain during acute stroke treatment was reported as 10.4% ( 37 ). While literature specific to the acute stroke unit has been scarce, studies focusing on rehabilitation outcomes in the subacute phase have indicated limitations imposed by malnutrition, as indicated by a decreased BMI ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the proportion of patients experiencing weight gain during acute stroke treatment was reported as 10.4% ( 37 ). While literature specific to the acute stroke unit has been scarce, studies focusing on rehabilitation outcomes in the subacute phase have indicated limitations imposed by malnutrition, as indicated by a decreased BMI ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nutritionists or dietitians may also guide dietary modifications to prevent future strokes and manage underlying medical conditions, such as diabetes or high blood pressure. For example, Kishimoto et al (2022) figured out that maintaining or gaining weight could be helpful during this stage in patients with a BMI lower than 30. Therefore, nutritional modifications have been extensively advised to inhibit immediate weight loss and observe better functional recovery.…”
Section: The Importance Of the Healthcare Team In Treating Stroke Casesmentioning
confidence: 99%
“…Recent weight change is more clinically important than the percentage of the ideal body weight. Kishimoto et al [ 16 ] found that, among 293 patients hospitalized for rehabilitation after stroke, the FIM score showed a tendency to improve in patients who maintained or increased their weight compared to those who lost over 5% of their weight in 6 months, and a positive correlation was identified between weight maintenance and higher intake compared to patients’ energy requirements [ 16 ]. In general, if an adult loses more than 5% of his or her weight within a month or 10% or more in 6 months, an overall assessment of nutritional status is required.…”
Section: Nutritional Assessments In Patients With Neurological Disordersmentioning
confidence: 99%